Breaking Monetary Policy News: The Role of Mass Media Coverage of ECB Announcements for Public Inflation Expectations - Patrick Hirsch; Lars P. Feld; Ekkehard A. Köhler (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using the variation in national television news of four major member states in the Eurozone, we find causal effects of coverage of high-frequency identified monetary policy announcements on households' inflation expectations in an event study and a generalized Difference-in-Differences approach with stacked data. If a monetary policy decision receives news coverage, the adaptation of inflation expectations is stronger than without coverage. Second, we find that coverage of 'delphic' monetary policy announcements, which are primarily informational in nature, leads to an inverse adjustment, i.e., expansionary shocks lead to households lowering their inflation expectations, as opposed to coverage of a textbook, 'odyssean', monetary policy shock.
Keywords: E31; E52; E58; C83; D84; 330; inflation expectations; media coverage; transmission of monetary policy; quasi-experimental evidence